Subluxação atlantoaxial canina - Freitas, Fernando de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The atlantoaxial subluxation or luxation is an instability of this articulation that produces excessive flexion of this joint causing the cranial aspect of the axis to rotate dorsally into the vertebral channel with subsequent spinal cord compression. This disorder is most commonly found in young small breed dogs. The diagnosis of this disease is done by survey radiographs, where there is a larger distance between the atlas dorsal arch and the axis spinal process characterize the atlantoaxial subluxation. Surgical stabilization is the treatment of choice and multiple implants show the best results to stabilize the atlantoaxial joint. The main complications are sudden death or implant failure. The sudden death happens because of cardiorespiratory arrest and it is most likely caused by brainstem iatrogenic trauma. However, a larger study comparing different surgical stabilization techniques should be performed to evaluate relative success rates in dogs that have the same initial neurologic status

subluxação ou luxação atlantoaxial é uma instabilidade dessa articulação que produz uma flexão excessiva fazendo com que o aspecto cranial do axis rotacione dorsalmente em relação ao canal vertebral com consequente compressão espinhal. Esta desordem é encontrada, na maioria dos casos, em cães jovens de raças pequenas. O diagnóstico dessa doença é feito por meio de radiografia simples onde o maior distanciamento entre o arco dorsal do atlas e o processo espinhoso do axis caracteriza a subluxação atlantoaxial. O tratamento de escolha é o cirúrgico, sendo, o uso de múltiplos implantes, a técnica que demonstrou melhor resultado para a estabilização da articulação atlantoaxial. As principais complicações do acesso ciúrgico são a morte súbita ou falha do implante. A morte ocorre devido à parada cardiorespiratória sendo a causa mais provável, um trauma iatrogênico no tronco encefálico. Porém um estudo maior, comparando diferenças de estabilizações cirúrgicas, deve ser realizado futuramente para avaliar o sucesso dos resultados, desde que em cães com o mesmo “status” neurológico inicial
Keywords: Cão - Doenças; Veterinaria